HUBUNGAN KEMAMPUAN MEMBACA APRESIATIF DENGAN KEMAMPUAN MENULIS TEKS CERPEN SISWA KELAS VII SMP - Rahayu Fitri (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the significant relationship between appreciative reading skills and the ability to write short stories for seventh grade students of junior high school. This type of research is quantitative research with correlational methods. The data obtained in this study were in the form of scores on the results of measurements on appreciative reading skills and scores on the results of measurements on students' ability to write short story texts. The populations in this study were all class VII students of SMP Negeri 25 Padang, totaling 254 students. The sampling technique used is a simple random technique. In this study, class VII C was chosen as the research sample because this class is a normal and homogeneous class. The numbers of samples in this study were 30 students. The data in this study were analyzed using a simple correlation test intended to test the research hypothesis. Based on the results of the study, it can be concluded that there is a significant relationship between appreciative reading skills and the ability to write short stories for class VII students of SMP Negeri 25 Padang. This can be seen from the results of tcount>ttable or 5.49>1.70.